A reforma curricular dos cursos de Pedagogia em Mato Grosso a partir das Diretrizes Curriculares Nacionais (DCNP) de 2006 - Silva, Silvana de Alencar (2015)
He research discusses the curriculum reform of Mato Grosso Education courses (MT) from the National Curriculum Guidelines for Education (DCPN) 2006. For this, it defines itself as an object of study the translation of DCPN held for six degree courses MV Pedagogy. The main objective was to understand the process of translation produced in MT Pedagogy courses from DCPN, with regard in particular to the senses and meanings enunciadores Pedagogy. The specific objectives were to identify the politicians and their curriculum demands articulated in the construction of PPC; analyze Pedagogy PPCs regarding its curriculum policy and characterize the discourse produced from the translation of DCPN in all the courses. The theoretical and methodological contributions were anchored in Bowe and Ball Policy Cycle (1994: 2001); Mainardes (2006); Lopes (2010); and the notion of Discourse Theory of translation Laclau (2011); Lopes Cunha and Costa (2013); and the contributions of Hall (1997; 2003). Research anchors the curriculum notion in Macedo (2006; 2011) Lopes (2010) and Silva (2011); of Curriculum Policy Ball (1994; 2001; 2011) and Macedo (2011) and reform in Lopes (2006); Oliveira (2004: 2009) and the initial training of teachers notion Tardif (2002); Garcia (1999) and Garcia, Hypólito and Vieira (2005). This is a qualitative research that takes as a source of data to the literature (OLIVEIRA, 2007) and documentary analysis (Cellard, 2008; SANTIAGO, 2008) of PPCs of Pedagogy. It is considered that the translation of DCPN by Degree courses in Pedagogy in MT was a negotiation process, marked by disagreements and Interim Agreements between the professional profile, the notion of curriculum and the meaning of pedagogy, because the courses needed to establish dialogue between its original identity with the identity proposed in DCPN. In this sense, the process of translation of the TM teaching courses indicates that disagreements demonstrate the instability of meaning which emphasizes the hybrid character of the PPC, crossed by contradictory demands between the formation of dedicated teacher for teaching in kindergarten and early years Elementary education and business management. In addition, teacher training models of notions of the investigated courses were based on the epistemology of traditional and critical practice. Since the courses situated in the critical perspective provide the construction of democratic management in school and beyond. Therefore, the translation of DCPN by teaching courses involved the context of the practice of agents, and suffered influences of other legislation, particularly the CNE / CP No. 01/02, which establishes the National Curriculum Guidelines for Training Education Teachers Basic.